Inovasi Eksipien Untuk Tablet Cepat Hancur - Muhammad hafiz adha; Nita Rahmadani; Anisa Nazwa; Khairatunnisa; Siti Noorlena (Jurnal Sains Farmasi Dan Kesehatan, 2024)
The main objective of this study is to review and explore various innovations in excipient materials used in the development of fast disintegrating tablets (FDT). This research utilizes the Systematic Literature Review (SLR) method, which is a comprehensive approach to systematically collect and analyze relevant literature. The results of the research indicate that overall, various studies have shown that innovations in tablet formulation, including excipient materials, production techniques, and drug delivery systems, significantly impact the effectiveness and comfort of drug use. The use of appropriate excipients, such as Biotapioka, avocado seed starch, and new technologies like edible paper and freeze drying, has been proven to address issues related to poor drug solubility and dissolution. With the right formulation, it is possible for tablets to disintegrate more rapidly in the mouth, allowing patients to experience the benefits of the medication more quickly, without the need for water or difficulty swallowing large tablets. This is especially important for patients who have trouble swallowing pills, such as the elderly, children, or patients with certain medical conditions.